On signatures of elliptic curves and modular forms - Dąbrowski, Andrzej; Pomykała, Jacek; Pujahari, Sudhir (The Ramanujan journal, 2023)
In [ 4 ], the first and second authors studied the signatures of Dirichlet characters and elliptic curves. In this paper we improve their lower bound estimates in the case of elliptic curves. We also introduce and investigate integral and interval d -constant signatures for cusp forms, and prove lower bound results for the number of twisted cusp forms having positive or negative signatures.